Halogen-free flame-retardant rigid polyurethane foam with a nitrogen–phosphorus flame retardant. (March 2017) - Zhao, Qianqiong; Chen, Congyan; Fan, Ruilan; Yuan, Yong; Xing, Yalin; Ma, Xiao
A halogen-free flame retardant containing nitrogen and phosphorus, 2-[anilino-(6-oxobenzo[c][2, 1]benzoxaphosphinin-6-yl)methyl]phenol (PDOP), has been synthesized by reaction of benzo[c][2, 1]benzoxaphosphinine-6-oxide (DOPO) with 2-( N -phenyliminomethyl)phenol. Halogen-free flame-retardant rigid polyurethane foams (RPUF-PDOP) were prepared using PDOP as a flame retardant. The flammability was investigated using limiting oxygen index, a vertical burning test (UL-94), and a cone calorimeter. When PDOP (10 wt%) as flame retardant was added to RPUF (RPUF-PDOP10% ), the limiting oxygen index value was increased from 18% to 27%, and a UL-94 V-0 rating was achieved; meanwhile, the peak heat release rate, total heat release, and the average mass-loss rates of RPUF-PDOP10% were reduced from 246 to 207 kW m −2, from 26.9 to 21.0 MJ/m 2, and from 0.043 to 0.033 g/s, respectively. Especially, the initial decomposition temperature of RPUF-PDOP10% was decreased from 228°C to 209°C. The final residual char from decomposition of RPUF-PDOP10% was significantly increased up to 35.6%. The addition of PDOP did not markedly decrease the mechanical properties of the resulting flame-retardant RPUFs.